DETERMINING THE WATER REQUIREMENT OF GROUNDNUT UNDER DIFFERENT IRRIGATION SYSTEMS AND IRRIGATION INTERVALS - Abdulrazzaq Saad Jabbar; Alaa Salih Ati (Iraqi journal of agricultural science, 2025)
Three field experiments were conducted in Al- Rashidiya region, Istiqlal district, north of Baghdad governate, to study the difference the irrigation interval under subsurface drip, sprinkler, and furrow irrigation systems in water requirement and yield of peanut (Arachis hypogaea L.) during the summer season 2021.Three field experiments were conducted, each including three irrigation systems, subsurface drip irrigation, sprinkler irrigation, and furrow irrigation. It was implemented as a Factorial experiment within the design of Nested-Factorial Experiments Design. Where the second factor distributed three irrigation intervals on the main plot (2-day, 4 day and 6 day), then the three factors were divided into four replicates in which the levels of organic fertilization under every system (control, 2000 kg ha-1 Orgevit fertilizer and 4000 kg ha-1 Orgevit fertilizer). The seasonal water consumption of peanut under the subsurface drip irrigation system at the irrigation intervals 2, 4, and 6 days were 362.34, 362.35, and 362.06 mm, respectively. The seasonal water consumption of peanut, calculated under the sprinkler irrigation system at irrigation intervals 2, 4 and 6 days, was 507.02, 507 and 505.63 mm, respectively. The seasonal water consumption of peanut under furrow irrigation at irrigation intervals 2, 4 and 6 on day 583.44, 584.88 and 583.35 mm, respectively. The average total yield of Peanut pods increases by 25% and 33.43% under furrow and subsurface drip irrigation system respectively compared to a sprinkler system.